Justice and Solidarity: Compound, Confound, Confuse (Diametros, 2015)
In response to Ruud ter Meulen’s contribution, it is argued that, although the relationship between these concepts is both tight and complex, solidarity should be carefully distinguished from justice.  Although ter Meulen wants to defend a normative conception of solidarity, the relation to its descriptive component is not always very clear. As a normative concept it should not collapse into that of justice; and as a descriptive notion it is obviously defective. In order to successfully navigate between these unhappy alternatives, ter Meulen rightfully turns to critical theory. But then it is still not entirely clear how the normative considerations that ter Meulen wants to defend follow from this promising framework.
Keywords: justice; solidarity; critical theory; health care; health insurance